2020
DOI: 10.3390/agronomy10111739
|View full text |Cite
|
Sign up to set email alerts
|

Design, Control, and Performance Aspects of Semi-Closed Greenhouses

Abstract: Several greenhouse energy saving technologies and management strategies have been developed in order to meet the needs for implementation of production systems with low and efficient energy use and low CO2 emissions. Towards this aim, a number of greenhouse concepts that make use of these technologies have been developed and tested, such as the closed greenhouse, the solar greenhouse, the energy-producing greenhouse, and others. The closed or semi-closed greenhouse concept is widely accepted as a concept to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The condensed water can be reused as irrigation water, and the water consumption will be furthermore reduced due to decreased evaporation losses via ventilation. The semi-closed operation of the greenhouse also reduces the risk of insect pests and fungal diseases [36]. An additional advantage is that the reduced ventilation leads to a better control of the CO 2 levels in the greenhouse.…”
Section: Novel Energy-efficient Greenhouse Conceptmentioning
confidence: 99%
“…The condensed water can be reused as irrigation water, and the water consumption will be furthermore reduced due to decreased evaporation losses via ventilation. The semi-closed operation of the greenhouse also reduces the risk of insect pests and fungal diseases [36]. An additional advantage is that the reduced ventilation leads to a better control of the CO 2 levels in the greenhouse.…”
Section: Novel Energy-efficient Greenhouse Conceptmentioning
confidence: 99%
“…Other benefits of semi-closed greenhouses could be a reduction in water consumption-due to the decreased transfer of water vapor towards the exterior environment via ventilation-and the decreased use of pesticides as a result of limiting the entrance of insects and the transmission of diseases [15]. Among the lines of improvement in the design of semi-closed greenhouses, the reduction in energy consumption in the distribution of air is underlined [16], as well as the development of refrigeration installations in greenhouses that are efficient in different climates, such as those found in continental, Mediterranean, tropical, and desert environments [17].…”
Section: Introductionmentioning
confidence: 99%
“…The transpiration intensity of tomato is closely related to the amount of irrigation, and many studies have found that ETc decreases with decreasing irrigation [2]. Therefore, reasonable irrigation regulation according to changes in the greenhouse environment and crop growth stage is an important means to ensure the growth of greenhouse crops [3]. Among them, the accurate and quick prediction of the transpiration rate (T r ) of greenhouse crops is the key to making irrigation regulation possible.…”
Section: Introductionmentioning
confidence: 99%